The Epidemiology of Anal Human Papillomavirus (HPV) in HIV-Positive and HIV-Negative Women and Men: A Ten-Year Retrospective Observational Study in Rome (Italy) - Matteo Fracella; Giuseppe Oliveto; Piergiorgio Roberto; Lilia Cinti; Massimo Gentile; Eleonora Coratti; Gabriella D’Ettorre; Eugenio Nelson Cavallari; Francesco Romano; Letizia Santinelli; Luca Maddaloni; Federica Frasca; et al. (Pathogens, 2024)
Human papillomaviruses (HPVs) commonly infect the anogenital mucosa; most infections are transient, but a fraction of those caused by high-risk (HR) types persist and may lead to anogenital cancer. The epidemiology of HPV genotypes in anal infections in groups at different risk for anal cancer has not been well described in Italy. This retrospective study reports the results of HPV DNA testing and complete genotyping performed on anal swabs from 691 female and male patients attending proctology clinics in Rome during 2012–2021; one-third had repeated testing. Cumulative HPV positivity in 1212 anal swabs was approximately 60%, was not age related, and showed an increasing trend over the study period. HPV rates differed significantly by sex and HIV status: HIV-negative women had the lowest (43.6%) and HIV-positive men the highest (83.5%) HPV prevalence. HIV-positive men had more oncogenic HPV genotypes detected, more multiple infections, and the highest frequency of persistent infections. Two-thirds of all infections were vaccine-preventable. This study found that anal HPV infection rates are still elevated and even increasing in groups at low and high risk of developing anal cancer. Prevention programs need to be improved to reduce rates of anal infection in young women and men.